VIOLATION OF MINERAL METABOLISM AS A PATHOPHYSI-OLOGIC PATHOGENIC MECHANISMS OF INFLAMMATORY PROCESSES IN PATIENTS WITH TUBERCULOSIS AND ITS CORRECTION - Зозуляк, В. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Objective was to study the clinico-biochemical features of dvsmicroelementosis at tuberculosis. Materials and methods. The clinico-radiological, laboratory, bronchological, bacteriological and biochemical data were studied in 421 patients. Besides, the essential microelements and dependent metal- loenzymes and metalloproteines metabolism and also free-radical reactions intensity and liver function indexes were studied in progress in 173 patients. Results and discussion. Microelements metabolism (Cu, Cr, Fe, Mg, Zn, Co, Cd, Li, K, Na), their daily balances, and also metalloenzymes activity: ceruloplasmin, catalase, carbonic anhydrase, iron and chrom saturation of transferin were studied in patients with destructive tuberculosis. Besides, free-radical reactions intensity (chemicoluminescence) was estimated in patients plasma. It was defined that patients under study develop dysmicroclementosis syndrom (internal microelements deficiency and increase of free-radical reactions intensity). The syndrom pathogenesis, diagnostics, clinic, treatment and prevention are described. Conclusions. Thus, sophisticated specific tuberculosis process causes significant alterations in all types of metabolism, what manifests in dvsmicroelementosis syndrome development. Dysmicroclementosis syndrome has its features of diagnostics, clinic, treatment and prophylaxis, and its timely detection and treatment improves more rapid and complete recovery of the patients.